PHYSICAL EXERCISE FOR POWER AND ENDURANCE VOLLEYBALL SPORT - Edy Dharma Putra Duhe (Universitas Negeri Gorontalo, 2020)
The research aims to provide a program of influence on the improvement of the dominant physical component in volleyball sports, the dominant physical component in question consisting of arm muscle strength, abdominal muscle strength, leg muscle strength, heart-lung endurance, and leg muscle explosion power. This type of research is experimental research, with the research design of One Group Pre-Test and Post-Test Design. The sample and population in this study were all male volleyball players from FOK-UNG with a total of 15 people. Treatment in this study is an exercise program that includes strength training, and heart-lung endurance performed 24 times. Based on the results of the study showed that there was a significant increase in each variable of the dominant physical component after being given the treatment program treatment.